The right to protest - Harris, Duchess (Harris, Duchess. American values and freedoms., 2018)
Examines the history of protest in the United States, from the first protest in Jamestown in 1619 to the modern age. Discusses why people protest, the different forms of protest, and what makes protests successful. Includes discussion questions in each chapter, a timeline, a glossary, resources for further information, and an index.